Treatment of fusiform aneurysms with a pipeline embolization device: a multicenter cohort study. (30th March 2022) - Turhon, Mirzat; Kang, Huibin; Li, Mengxing; Liu, Jian; Zhang, Yisen; Zhang, Ying; Huang, Jiliang; Luo, Bin; Liu, Jianmin; Zhang, Hongqi; Li, Tianxiao; Song, Donglei; et al.
Abstract : Background: Intracranial fusiform aneurysms are less common than saccular aneurysms, but are associated with higher mortality and morbidity. We conducted this study to determine the safety and efficacy of the pipeline embolization device (PED) to treat intracranial fusiform aneurysms. Methods: This was a multicenter, retrospective, and observational study. Data for this study came from the PLUS study conducted from 2014 to 2019 across 14 centers in China. Univariate and multivariable logistic regression analyses were performed to evaluate predictors of the occlusion rate and complication. Results: A total of 1171 consecutive patients with 1322 intracranial aneurysms participated in this study. Among the participants, 104 patients with 109 fusiform aneurysms were eligible for this analysis (mean age 49 years, 36.5% women, aneurysm mean size 14.7 mm, 55% in the posterior circulation, and 6% in the basilar artery). Mean follow-up time was 9.0 months (range 3–36 months). The last DSA angiographic follow-up was available for 85 patients, and 58 aneurysms (68.2%) were completely occluded. The overall complication rate and mortality were 17.3% and 2.8%, respectively. Multivariate analysis demonstrated that age (OR=1.007, p=0.037) and cerebral atherosclerosis (OR=1.441, p=0.002) were associated with incomplete occlusion of fusiform aneurysms after PED treatment. Conclusion: PEDs may be an effective treatment for intracranial fusiform aneurysms, with a favorable occlusion rate. However, because these treatments have a relatively high rate of complications, PED treatment for fusiform aneurysms should be carefully and strictly controlled. Our analysis showed that PEDs with adjunctive coiling did not significantly improve the occlusion rate of fusiform aneurysms.